Exploring the trajectory of post-traumatic growth in patients in intensive care unit: a phenomenological longitudinal study - Hongyi Li; Xue Li; Yuying Fan; Jingshu Li; Xiaona Qi (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Post-traumatic growth (PTG) has been increasingly observed in various trauma groups. However, few studies have longitudinally explored PTG in intensive care unit (ICU) patients using qualitative methods. This study aimed to explore PTG pathways in ICU patients and offer reference data and methodological insights for personalized interventions. Methods A phenomenological longitudinal study was conducted among patients transferred from ICU between May 2023 and February 2024. Four interview points were determined: Day two after transfer to ICU (T0), the 1st month after transfer out of ICU (T1), the 3rd month after transfer out of ICU (T2), and the 6th month after transfer out of ICU (T3). Results 21 cases were included. Two PTG trajectories were identified: “sublimation PTG trajectory” and “compound dual-path PTG trajectory,” comprising four periods: “trauma response,” “growth transition,” “collapse,” and “transition recovery.” Fifteen themes emerged, including “the persistent presence of avoidance responses,” with details shown in figures and tables. Conclusions PTG in ICU patients showed shared and individualized patterns. Clinicians should recognize key time points, support self-healing, and tailor extended care. A multidisciplinary aftercare model combining online and in-person services is recommended for long-term recovery.